2003
DOI: 10.1021/es026039g
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Enantiomeric Fractions during Microbial Reductive Dechlorination of PCB132, PCB149, and Aroclor 1254 in Lake Hartwell Sediment Microcosms

Abstract: The enantioselectivity of microbial reductive dechlorination of chiral PCBs in sediments from Lake Hartwell, SC, was determined by microcosm studies and enantiomer-specific GC analysis. Sediments from two locations in the vicinity of the highest levels of PCB contamination were used as inocula. Dechlorination activity was monitored by concentration decreases in the spiked chiral PCBs and formation of dechlorination products using both achiral and chiral chromatography. Live microcosms spiked with PCB132 (234-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 38 publications
11
48
0
Order By: Relevance
“…The latter congeners exist as stable enantiomers, and we wondered whether their dechlorination would be limited. Stereoisomers of PCBs exist as racemic mixtures in commercial PCBs, and evidence for stereoselective dechlorination of some PCB congeners has been reported (52,67). Our data show that there was well over 50% dechlorination of 236-236-CB, 236-245-CB, 2356-245-CB, and 2345-236-CB, demonstrating that both stereoisomers of each of these congeners are dechlorinated.…”
Section: Discussionsupporting
confidence: 56%
“…The latter congeners exist as stable enantiomers, and we wondered whether their dechlorination would be limited. Stereoisomers of PCBs exist as racemic mixtures in commercial PCBs, and evidence for stereoselective dechlorination of some PCB congeners has been reported (52,67). Our data show that there was well over 50% dechlorination of 236-236-CB, 236-245-CB, 2356-245-CB, and 2345-236-CB, demonstrating that both stereoisomers of each of these congeners are dechlorinated.…”
Section: Discussionsupporting
confidence: 56%
“…Microcosms with sediments from the same cores [156] spiked with racemic PCB 132 reductively meta-dechlorinated this congener nonenantioselectively to PCB 91, which in turn was stereoselectively metadechlorinated to achiral PCB 51 ( Figure 4.12). Similarly, PCB 149 was nonstereoselectively para-dechlorinated to PCB 95, in turn enantioselectively meta-dechlorinated to achiral PCB 53 [163]. The enantiomer preferences for PCB 149 dechlorination were consistent between the laboratory microcosms [163] and field observations, suggesting possible similarities in the microbial consortia in both cases.…”
Section: Pcbssupporting
confidence: 51%
“…Similarly, PCB 149 was nonstereoselectively para-dechlorinated to PCB 95, in turn enantioselectively meta-dechlorinated to achiral PCB 53 [163]. The enantiomer preferences for PCB 149 dechlorination were consistent between the laboratory microcosms [163] and field observations, suggesting possible similarities in the microbial consortia in both cases. However, PCB 132 was nonracemic in the cores [156], suggesting that either the microbial consortia and/or environmental conditions affecting microbial activity were different between the laboratory and in situ.…”
Section: Pcbssupporting
confidence: 51%
See 1 more Smart Citation
“…Singer et al [36] found that PCB 95 was less likely to undergo aerobic biotransformation than PCB 91 with pure cultures under ideal laboratory conditions. Previous work with microcosms incubated with sediment from Lake Hartwell indicated that both chiral congeners could undergo anaerobic biotransformation [37]. On the other hand, similarity in EF values in the PEs among the sites does not provide any strong evidence to indicate additional inputs of PCB to the system.…”
Section: Chiral Signaturesmentioning
confidence: 73%